Application Of Cooperative Script Learning To Increase Science Learning Outcomes For View Class Students Of SD Negeri 0802 Tamiang T.P 2020/2021 - Hotmatua Nst (Indonesian Journal of Basic Education, 2021)
The background of this research is the low student learning outcomes in the subjects of Natural Sciences. Meanwhile, the purpose of this study was to improve learning outcomes of natural science students in class VI of the State Elementary School 0802 Tamiang by using a written opinion submission technique strategy. This research is a type of classroom action research with the research subjects being teachers and students of class VI of the State Elementary School 0802 Tamiang with a total of 24 students. While the object of this research is the application of cooperative script learning model to improve learning outcomes of Natural Sciences (IPA) on the subject of the earth and the universe. Data collection techniques using observation and tests. Based on the results of the study, it was concluded that the application of the Cooperative Script learning model could improve the mathematics learning outcomes of the sixth graders of the 0802 Tamiang State Elementary School. This increase is based on the classical percentage obtained from pre-action, which is 41.67% reaching the KKM, increasing in the next cycle which is 70.83% in the first cycle with an average student learning outcome reaching 75 in good category, and in the second cycle into a very good category with classical completeness that is 91.67% of the total number of students in the class and is in the range of 81%-100%, with an average student learning outcome of 83.67